PENGEMBANGAN BISKUIT KENARI (Canarium indicum L) BERBAHAN BAKU TEPUNG SAGU BARUK (Arenga microcarpa) - Veybi S. Makanoneng; Ir. Erny J.N. Nurali, MS.; Dr.Ir. Gregoria S.S. Djarkasi, MS. (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ The purposes of this research was to evaluate the sensory quality of â€œkenariâ€ biscuits that made from mixingof sago â€œbarukâ€and corn starch;Â and to analyze the chemical content of a â€œkenariâ€Â biscuits that have the highest percentage by panelists. This research was designed using Complete Randomized Design with four treatments with three replications each treatment. Those are (A) 90 g sago baruk and 10 g cornstarch, (B) 85 g sago baruk and 15 g cornstarch, (C) 70 g sago baruk and 20 g cornstarch and (D)75 g sago baruk and 25 g cornstarch. The results showed that the â€œkenariâ€ biscuits that made from sago baruk 90 g and 10 g cornstarch has the highest percentage given by panelists. That biscuit contents 6.66% of moist, 1.46% of ash, 8.96% of protein, 42.28% of fat, 40.6% of carbohydrates and 578.92 calorie Keywords: Sago baruk, Kenari nuts, biscuit.